The Relationship between Self-Confidence and Participation of Dance Participants at Sanggar Seni Ateh Tabiang Bukittinggi City - Pertiwi, Putri; Jamaris, Jamaris (Universitas Negeri Padang, 2024)
This research was motivated by the low participation of dance participants at the Sanggar Seni Ateh Tabiang, which was thought to be caused by the participants' lack of self-confidence. This research aims to determine the level of participants self-confidence, participation dance participants', and determine the relationship between self-confidence and the participation of dance training participants at the Sanggar Seni Ateh Tabiang. The research method uses a quantitative approach with a correlational research type. The population of this study was all dance training participants registered at the Sanggar Seni Ateh Tabiang. Sampling used the Simple Random Sampling technique. The data collection technique uses a questionnaire. Data analysis techniques use percentage formulas and Product Moment formulas. The research results show that; participants' self-confidence was categorized as low; participant participation was categorized as low; and there is a significant relationship between self-confidence and participant participation. The suggestion is that it is hoped that the participants' mental development will strengthen their self-confidence; It is hoped that participants will increase their participation to actively practice so that their mastery of dancing skills increases; and in practice, participants' participation should be paid attention to during practice because actively practicing will improve dancing skills and thus also increase participants' self-confidence. Keywords: Self-Confidence, Participant Participation